The Role of Financial Literacy, Accounting Literacy, and Digital Literacy in Improving the Managerial Ability of MSMEs - Metyria Imelda Hutabarat; Ahmad Kamal Jama; Aninditha Putri Kusumawardhani (Yayasan Kawanad, 2025)
Understanding financial management, accounting reporting, and digital technology utilization can enhance the quality of business managerial capabilities. This study examines the role of financial literacy, accounting literacy, and digital literacy in improving managerial capabilities of MSMEs. Partial results demonstrate that financial literacy, accounting literacy, and digital literacy exert positive and significant effects on managerial capabilities of MSMEs in Medan City. Simultaneous results indicate that financial literacy, accounting literacy, and digital literacy collectively exert positive and significant effects on managerial capabilities of MSMEs in Medan City. MSMEs in Medan City gain greater opportunities to strengthen their competitiveness and business sustainability. The Adjusted R Square value reaches 45.1%, while the remaining 54.9% stems from variables beyond the research model, including entrepreneurial behavior among others. Research findings necessitate support from local governments, educational institutions, and relevant stakeholders to enhance training and mentoring programs in financial, accounting, and digital literacy for MSMEs, thereby strengthening managerial capacity and fostering economic growth in Medan City.